Gender Phenomenon in Short Story by Fanny J. Poyk in Media on Line, Indonesia - Juanda Juanda (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study discuss contemporary feminist genres and innovative techniques PoyK and social issues, traditional and modern culture of women in the short story. Analysis of descriptive data through library data, relevant research journal articles, online newspapers, short story Fanny J. Poyk